Contemporary Issues of the Judiciary’s Development - RYSZHANOVA, Gulnur; KOZHAKHMETOV, Galym (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The article explores the role of the judiciary in the mechanism of the division of powers in Kazakhstan. The authors studied issues of ensuring judiciary’s independency: discrepancy of norms in the current legislation, related to the questions of the judges’ independency; the dependency of the judiciary on executive and legislative powers in the questions of financing. The article examines the necessity of raising the level of judges’ legal culture. The authors have proposed specific recommendations for the improvements of judiciary’s development in Kazakhstan.